Presence of the Reflective and Critical Thinking Capacity in Nursing Curricula in Iberian America - Lucila Cárdenas Becerril; María Antonia Jiménez-Gómez; María Dolores Bardallo-Porras; Jesús López-Ortega; Araceli Monroy-Rojas; Vilanice Alves de Araújo-Püschel (Universidad de Antioquia, 2020)
Objective. The objective was to identify the presence of the capacity for reflexive-critical thinking or similar, in Nursing Curricula in Iberian America. Methods. The article gathers the results of one of the objectives of the macro-project developed by the Iberian American Network on Nursing Education Research, titled Strategies to develop reflective and critical thinking in nursing students: Iberian America situation. To achieve this, a descriptive and exploratory research was conducted with qualitative approach. An instrument created for this project was used, along with some guiding questions to focus the information. Results. Eight countries participated (Bolivia, Brazil, Colombia, Ecuador, Spain, Mexico, Peru, and Venezuela), which contributed information from 189 curricular plans. The R&CT was found in the majority of the curricula, although with diverse denominations. The principal learning strategies used were problem-based learning, group dynamics, reflective reading, clinical practice, and simulation laboratories. The evaluation methods used are the knowledge test, case analysis, and practical exam. Conclusion. Significant stress exists in the discourse and curricular organization. Incongruences were found and a clear inclination toward the formation of professionals with broad technical skills under a traditional, memory, banking and knowledge accumulation education.